(untitled) - Ballon, Robert J. (Tokyo, 1967)
Contents: Part I. Entering the japanese economy; Part II. Writing the joint-venture contract; Part III. Managing the joint venture; Part IV. Marketing the joint venture
Keywords: Investments, foreign,Đầu tư nước ngoài; Japan,Nhật Bản